ANALISIS DAN PREVENTIF LIKUEFAKSI DENGAN METODE KOLOM SEMEN (LIQUEFACTION ANALYSIS AND PREVENTION USING CEMENT COLUMN METHOD) - liliwarti liliwarti; Satwarnirat -; Silvianengsih -; Dwina Archenita (Direktorat Bina Teknik Jalan dan Jembatan, 2018)
Liquefaction is the loss of soil strength due to an earthquake. Liquefaction usually occurs on the water-saturated soil, pore water pressure increases and the soil loses its bearing capacity ,consequently it can not support heavy structure which cause the building collapses. Padang is an earthquake-prone area that has caused several damage (Earthquake in Padang on September 2009), many buildings and infrastructures have collapsed, its was due to the liquefaction triggered by the earthquake. Analysis and prevention of liquefaction is needed to minimize the impact of the earthquake. This study liquefaction analysis uses the CPT, and the prevention of liquefaction by the cement column method. The results of liquefaction analysis consisting of 10 locations which were observed shows that there were 4 points location of potentially liquefaction, 3 points of hight liquefaction and 3 points that didn’t potentially liquefaction. The cement column method is carried in a laboratory by means, the soil sample is placed in a test box and then grouting by cement with a diameter 2.5 cm, with spacing 2D, 3D and 4D. The test box was vibrated and then shear strength was tested after and before grouting. The results of shear strength test obtained cement column can reduce the potential liquefaction with the spacing is 2D. The shear streght value increas from 3.14 kPa to 16.86 kPa, the shear strength value increased by 537% ,and can reduce the settlement by 500%. The results of this study can be utilized by consultants and the government to guideline development of Padang city. Keywords: soil, earthquake, liquefaction, CPT, cement column